Rapid Induction of Neuronal Phenotypes in Mesenchymal Stem Cells: A Morphological Observation - Maizatul Fazilah, Abd Razak; Muna, Sabri (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2025)
ABSTRACT